Kontroversi Fatwa Astrazeneca: Kontestasi Atau Harmonisasi? - Shofiyullah Muzammil; Perdana Putra Pangestu (Asy-Syari'ah, 2023)
The fatwas difference occurred between the Central MUI and the regionsover the legal assessment of the AstraZeneca Vaccine containing pork trypsin in the manufacturing process; this later became a discussion on the halal status and sanctity of the vaccine. This study examines how fatwa contestation can occur internally at MUI and what realistic steps must be taken by the Indonesian government and MUI to control increasingly excessive issues. This research is packaged through library research by basing the analysis on relevant and correlative sources. Primary data is taken from the fatwa decision document No. 14 Tahun 2021 Tentang Hukum Penggunaan Vaksin Covid-19 Produk AstraZeneca by MUI. Secondary data is obtained through news reports, public media channels and other literature that still has a strong relationship with the main issue. This study concludes that MUI must consolidate, standardize and consider various perspectives in drawing the right conclusions and not causing public commotion and doubt.